Physiology and methodology of chromium toxicity using alga Scenedesmus quadricauda as model object - Kováčik, Jozef; Babula, Petr; Hedbavny, Josef; Kryštofová, Olga; Provaznik, Ivo (Chemosphere, 2015)
Physiological responses of Scenedesmus quadricauda to Cr(VI) and Cr(III) excess were studied in buffer with circumneutral pH (6.5). Total Cr content was similar in low (1 μM of both oxidation states) but higher in 10 μM Cr(VI) treatment and high accumulation potential was detected (80-82% and 41-65% in 1 and 10 μM treatments, respectively). Specific fluorescence indicator (6-((anthracen-9-yl) methyleneamino)-2H-chromen-2-one) confirmed partial reduction of Cr(VI) to Cr(III) under exposure conditions. Viability and chlorophyll autofluorescence were more depleted by Cr(VI) while Cr(III) stimulated increase in ROS and lipid peroxidation. Antioxidative enzyme activities showed significantly higher values in 10 μM treatments of both Cr oxidation states. Depletion of mitochondrial proteins was not reflected in alteration of total soluble proteins indicating sensitivity of this organelle to Cr and TTC test showed no clear oxidation state-related effect. In this view, "Cr(VI) is not more toxic than Cr(III)" at least for some parameters. Subsequent study with the application of 10 μM Cr(VI) confirmed that HEPES buffer is more suitable exposure solution for toxicological studied than water or inorganic salts (higher chlorophyll autofluorescence was observed) and pH 6.5 is more suitable than low or high pH (4.5 or 8.5) in terms of Cr uptake. Another known Cr(III) fluorescence indicator (naphthalimide-rhodamine) also confirmed partial reduction of Cr(VI) to Cr(III) at acidic pH but only traces were seen at alkaline pH.
Keywords: reaktivní formy kyslíku; látky znečišťující životní prostředí; Chlorophyll; Hydrogen-Ion Concentration; mitochondriální proteiny; Fluorescence; koncentrace vodíkových iontů; oxidace-redukce; Mitochondrial Proteins; Reactive Oxygen Species; chlorofyl; peroxidace lipidů; Environmental Pollutants; Lipid Peroxidation; Oxidation-Reduction; chrom; fluorescence; Chromium; Scenedesmus